2022
DOI: 10.1007/s11356-022-19000-9
|View full text |Cite
|
Sign up to set email alerts
|

Do economic policy uncertainty and environment-related technologies help in limiting ecological footprint?

Abstract: Economic policies related to energy and the environment are found uncertain in developing economies. Renewable energy sources are gradually increasing in energy structure (ES) with the adoption of environment-related technologies (ERT). However, least attention is paid to investigating the nexus of economic policy uncertainty (EPU), ERT, ES, and ecological footprint (EF). Therefore, this study is an effort to examine the EPU, ERT, ES, and interaction of EPU and ERT on EF for BRICS economies under the umbrella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 44 publications
(50 reference statements)
2
7
0
1
Order By: Relevance
“…It means that energy structure is helpful to reduce ecological footprints in E7 economies. Previous studies have shown similar results (Bilal et al 2022 ; Hussain et al 2022 ).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…It means that energy structure is helpful to reduce ecological footprints in E7 economies. Previous studies have shown similar results (Bilal et al 2022 ; Hussain et al 2022 ).…”
Section: Resultssupporting
confidence: 75%
“…Moreover, another challenge faced by the world is to manage uncertain economic policies for sustainable development and a clean environment. According to recent studies on economic policy uncertainty (EPU), it is a serious issue to be considered to control environmental degradation (Hussain et al 2022 ; Syed et al 2022 ). In developing countries, uncertain economic policies lead to confused investors and manufacturers about their returns.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) utilized the STIRPAT model to examine the Kyoto Protocol's pledges on carbon dioxide emissions and the factors that contribute to environmental degradation. According to Hussain et al. (2022) , in a study done in the BRICS economies, consistent economic policies are needed to fully realize the benefits of environmental technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Darsono et al (2022) find that EPU reduces sustainable stock market returns in the long run and discourages investment activity. Further, EPU reduces investment in environmental technologies in industrial production, increasing the ecological footprint in the long run (Hussain et al 2022). At the same time, renewable energy use and R&D decrease as EPU increases (Amin andDogan 2021, Shafiullah et al 2021).…”
Section: Environmental Impact Of Epumentioning
confidence: 99%